Oxylipin Signaling: A Distinct Role for the Jasmonic Acid Precursor cis-(+)-12-Oxo-Phytodienoic Acid (cis-OPDA) - Dave, Anuja; Graham, Ian A. (Frontiers in Plant Science, 2012)
Oxylipins are lipid-derived compounds, many of which act as signals in the plant response to biotic and abiotic stress. They include the phytohormone jasmonic acid (JA) and related jasmonate metabolites 12-oxo-phytodienoic acid (OPDA), methyl jasmonate and jasmonoyl-L-isoleucine. Besides the defense response jasmonates are involved in plant growth and development and regulate a range of processes including glandular trichome development, reproduction, root growth and senescence. OPDA is known to possess a signalling role distinct from JA. The non-enzymatically derived phytoprostanes are structurally similar to OPDA and induce a common set of genes that are not responsive to JA in Arabidopsis thaliana. A novel role for OPDA in seed germination regulation has recently been uncovered based on evidence from double mutants and feeding experiments showing that OPDA interacts with abscisic acid (ABA), inhibits seed germination and increases ABI5 protein abundance. Large amounts of OPDA are esterified to galactolipids in Arabidopsis thaliana and the resulting compounds, known as Arabidopsides, are thought to act as a rapidly available source of OPDA.